Social & Economic Conflict Analysis of The Main Character on The Pursuit of Happiness Movie : A Marxism Analysis - Dimas Fisal B; Faishal Arkan (Universitas An Nuur, 2021)
Marxism is the system of socialism of which the dominant feature is public ownership of the means of production, distribution, and exchange. Same as with the problem of this film one of the sociological problem of this film is the father have no money to give his children some happiness, homeless and always confused to eat everyday as we know economical problem is the big problem.While Marx and Engels wrote little on education, the educational implications of Marxism are clear. Education both reproduces capitalism and has the potential to undermine it. With respect to reproduction, it is informative to look at key texts by Althusser and Bowles and Gintis (and the latter’s legacy). As far as challenging capitalism is concerned, considerations are given to both theoretical developments and practical attempts to confront neoliberalism and enact socialist principles.